2019
DOI: 10.9734/ijtdh/2019/v35i330124
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella pertussis: Vaccine Coverage and Immune Status among Children Under Five Years Old in Sana’a City, Yemen

Abstract: Aims:This study was made to evaluate the immune response to pertussis among children under five years old by measuring the level of circulating Immunoglobulin G (IgG) antibodies against pertussis toxin (IgG-PT) after immunization with the primary series of DPT (DPT1-3) and then determining the coverage rates of universal childhood vaccines. Study Design: Cross-sectional laboratory study. Place and Duration of Study: Methodology: A total of 345 children were randomly selected and investigated for universal chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 19 publications
3
11
2
Order By: Relevance
“…Reports of the Center for Diseases Control and Prevention[ 23 ] and American Academy of Pediatrics Infectious Diseases[ 24 ] showed that three times infusion of HBV vaccine caused the occurrence of protective antibody in 85%–100% of people which was higher than our report. The levels of immunity against vaccination with recombinant hepatitis B vaccine in a study which was conducted in Yemen[ 25 ] and those of Iran[ 26 27 28 ] had ranges of 50%–80% which was higher than our findings. Several studies have been reported that immune response to hepatitis B vaccine is depended on host factors such as sex, age, weight, genetics, and immunocompetent of individuals.…”
Section: Discussioncontrasting
confidence: 92%
“…Reports of the Center for Diseases Control and Prevention[ 23 ] and American Academy of Pediatrics Infectious Diseases[ 24 ] showed that three times infusion of HBV vaccine caused the occurrence of protective antibody in 85%–100% of people which was higher than our report. The levels of immunity against vaccination with recombinant hepatitis B vaccine in a study which was conducted in Yemen[ 25 ] and those of Iran[ 26 27 28 ] had ranges of 50%–80% which was higher than our findings. Several studies have been reported that immune response to hepatitis B vaccine is depended on host factors such as sex, age, weight, genetics, and immunocompetent of individuals.…”
Section: Discussioncontrasting
confidence: 92%
“…The low correlation value was due to the weaker protective response of the one to <2 years old group compared to the older age group. This finding was supported by previous reports of declined HBV vaccine protective level with age in Yemen [13, 19]. Similar association between older age and lower level of HBV vaccine protection rate has been reported by studies conducted in Saudi Arabia [36], Europe [37], and China [38, 39].…”
Section: Discussionsupporting
confidence: 90%
“…This HBV vaccine seroprotective rate was higher than the rate reported in children <1–10 years old by Al Shamahy and coworkers in Sana'a 5 years ago [13]. However, it was lower than that reported by Sallam and coworkers from Sana'a in 2005 [20].…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations